TEM Study of ODS Alloy Doped with Helium Ions and Re-irradiated with Swift Xe Ions - Tiep, N V; Khiem, L. H.; Sohatsky, A. S.; Skuratov, V. A.; Van Vuuren, A. J.; O’Connell, J. H.; Zdorovets, M. (Communications in Physics, 2019)
Oxide dispersion strengthened (ODS) alloys are considered as candidates for fuel assembly claddings, since nano-oxides, among other things, contribute to the gas swelling suppression. However, it is still unknown that how oxides will behave in this capacity under the exposure to fission fragments. Transmission electron microscopy has been applied to study helium porosity in a ferritic EP450ODS alloy doped with helium by the ion implantation and re-irradiated with high energy Xe ions, which is used for simulating fission fragments at room temperature followed by annealing. It has been shown that helium bubbles mainly decorate the structural defects and grain boundaries both in helium doped only and in re-irradiated with Xe samples. Furthermore, we have found that there was not significant changes in the size distributions of helium bubbles in ferritic matrix due to the re-irradiation with Xe. The only effect of irradiation with swift Xe ions on the alloy structure is the amorphization of dispersed oxides in it. But, as a result of amorphization of dispersed oxides, helium bubbles were detected at the oxide-matrix (O-M) interfaces as well as inside amorphous oxides, while they have not been observed inside crystalline nano-oxides and seldom connecting to the O-M interface in the He-doped only samples. That means the nano-oxides amorphized by fission fragments can promote the better helium bubbles pinning in actual operation of the fuel assembly cladding in a nuclear reactor.